Standardization of a scale for social competence of children aged 4–6 years; A field study in kindergartens in the interior regions of Israel - Nahle, Ehlas Ibrahem (Journal of Educational and Psychological Sciences, 2025)
This study aimed to develop and standardize a scale to assess social competence among typically developing children aged 4 to 6 years in the Arab communities within the Green Line (1948 territories). The initial version of the scale consisted of 79 items across three domains: communication skills, social participation, and self-regulation. Using a descriptive survey methodology, the scale was applied to a sample of 42 kindergarten nannies of the Al-Ghuraba Association in the city of Araba Al-Batuf, whose chronological age ranges from (4-6).. The psychometric properties were examined using Cronbach’s alpha, split-half reliability, and factor analysis. The results indicated strong internal consistency and construct validity. The study recommends broader application of the scale across various sociocultural contexts, its integration into educational programs, and the development of digital tools for ease of administration.
Keywords: social competence; communication skills; social participation; self-regulation; preschool children; Arab communities in Israel